2010
DOI: 10.1055/s-0030-1249034
|View full text |Cite
|
Sign up to set email alerts
|

Bupropion-Associated Premature Ejaculation

Abstract: This paper describes two case reports of bupropion-associated premature ejaculation. Two men (aged 37 and 39) were treated for residual symptoms of depression. At 300 mg / day of bupropion, they ejaculated in under a minute, compared to a normal time of three to four minutes. This was present for several months. With the 37-year-old man, the time normalized after adding escitalopram. With the 39-year-old man, it spontaneously increased to two minutes after fi ve months. Although bupropion is reported to be fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Anecdotal reports also mentioned cases of acquired PE following withdrawal of SSRI medication (e.g. citalopram) [34] or use of the norepinephrine and dopamine reuptake inhibitor bupropion [35].…”
Section: Pharmacological Factorsmentioning
confidence: 99%
“…Anecdotal reports also mentioned cases of acquired PE following withdrawal of SSRI medication (e.g. citalopram) [34] or use of the norepinephrine and dopamine reuptake inhibitor bupropion [35].…”
Section: Pharmacological Factorsmentioning
confidence: 99%
“…The rationale for using bupropion in DE comes from the following observations: (I) it has been shown that chronic bupropion administration at high doses alters the function of the spinal generator for ejaculation (SGE) in rats (24); (II) bupropion produces concentration- dependent increases in the contractile response to nerve stimulation in the rat vas deferens and significantly increases the pressor response to noradrenaline suggesting facilitatory action of the ejaculatory reflex (25); (III) in vitro bupropion increases by eight-fold the NE potency in inducing contractions of the epididymal duct from untreated rats. The ability of bupropion to enhance epididymal duct contractions to NE is due to its action as a NE transporter blocker as bupropion did not change duct contraction to methoxamine (26); (IV) bupropion has been demonstrated to induce premature ejaculation in 46 years old man after the use of 150 mg bupropion per day for depression and premature ejaculation disappeared two weeks after stopping of bupropion (27,28); and (V) bupropion showed prosexual effects when compared with the other antidepressants and no patient taking bupropion complained of delayed orgasm (29). Most of the studies have noted that bupropion is not only as effective as other antidepressants but has the advantage of a lower impact on the sexual function.…”
Section: Bupropionmentioning
confidence: 99%